Amoxycillin Injection in the Treatment of Pyogenic Meningitis in Children. (March 1979) - Maguire, M J; Khan, A A
An open trial of the use of amoxycillin injection in the treatment of pyogenic meningitis in children showed similar results to previous trials here of penicillin-chloramphenicol combinations. It is felt that, in developing countries at least, treatment of pyogenic meningitis in children should be with the latter combination, but where rapid and accurate bacteriology is available amoxycillin may be a valuable non-toxic alternative to chloramphenicol with similar activity to ampicillin.